2009
DOI: 10.1111/j.1365-2494.2008.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rates and timing of application of nitrogen as slurry and mineral fertilizer on yield of herbage and nitrate‐leaching potential of a maize/Italian ryegrass cropping system in north‐west Portugal

Abstract: Efficient use of cattle-slurry to avoid nitrogen (N) leaching and other losses is important in designing intensive dairy systems to minimize pollution of air and water. The response in dry-matter (DM) yield of herbage and nitrate-leaching potential to different rates and timing of application of N as cattle slurry and ⁄ or mineral fertilizer in a double-cropping system producing maize (Zea mays L.) silage and Italian ryegrass (Lolium multiflorum Lam.) was investigated in north-west Portugal. Nine treatments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…The double-cropping system yield and N uptake in this study was not as high as that reported in other Italian (Onofrii et al, 1993) and Portuguese (Trindade et al, 2008) studies; in those instances, maize produced 10-20% more biomass. The yields and uptakes of grass leys were also similar to those obtained in local farm…”
Section: Observed N Uptake Values Between 224contrasting
confidence: 67%
“…The double-cropping system yield and N uptake in this study was not as high as that reported in other Italian (Onofrii et al, 1993) and Portuguese (Trindade et al, 2008) studies; in those instances, maize produced 10-20% more biomass. The yields and uptakes of grass leys were also similar to those obtained in local farm…”
Section: Observed N Uptake Values Between 224contrasting
confidence: 67%
“…NO 3´p ollution is a relevant issue for intensive livestock farms where liquid and solid manure as organic effluents are used [22][23][24][25]. NO 3´l eaching is particularly serious in Mediterranean semi-arid countries [23,26], where substantial N losses by leaching were found to occur during the rainy period in winter and after irrigation practice in summer. To date, the relationships between soil NO 3´a ccumulation and groundwater NO 3ć oncentrations in agricultural soils are still not entirely understood [1].…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those obtained by Trindade et al . () in a double‐cropping system when producing maize and ryegrass, in north‐western Portugal, in which it was necessary to apply more than 400 kg N ha −1 year −1 from organic materials in order to obtain high yields. In addition, it is not unusual in the study area to find that the first organic applications, after years without them, can cause soil mineral N immobilization (Domingo Olivé et al ., , ) to balance the C/N ratio of the organic matter applied and that from the soil.…”
Section: Discussionmentioning
confidence: 74%
“…Trindade et al . (), in a rotation of maize (silage) with Italian ryegrass (forage), determined an annual rate of up to 250 kg available N ha −1 from slurry as the requirement to obtain high productivity while also minimizing leaching losses. Nevertheless, in humid Mediterranean environments, data on N efficiency and NFRV of manures are still lacking for situations when a double‐annual cropping rotation is implemented and the crops are harvested as fodder.…”
Section: Introductionmentioning
confidence: 87%